Implementasi Quick Sort pada Cluster Computer menggunakan Raspberry Pi 3 - Igo Vicky Firmandia; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
A cluster computer is a type of parallel or distributed processing system that consists of a collection of stand-alone computers that are connected and work together as one integrated resource (Morrrison, 2003). Cluster computers can be implemented for specific purposes, and using parallel processing methods such as MPI4PY (Message Passing Interface for Python) MPI4PY is used to execute parallel programs into subtasks, then send them to the cluster nodes for processing. This research focuses on designing, implementing, and knowing the performance produced by computer clusters using raspberry pi 3. To find out the resulting performance, a scheme is tested using a master node without a slave, one slave master node, two slave master nodes, and a master node. three slaves. The monitoring process is carried out using ganglia to determine the size of cluster resource usage. The monitoring results show the highest memory usages of 818.8M in 109 iterations of testing the master node and 2 slave nodes. The highest loads/process was 14.1 in 109 iterations of testing using only the master node. The highest CPU usages were 32.7% in iteration 109 tests the master node and 2 slave nodes.